2009
DOI: 10.1111/j.1475-4991.2008.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Measurement With Discrete Proxy Variables: Is Principal Component Analysis a Reliable Answer?

Abstract: The last several years have seen a growth in the number of publications in economics that use principal component analysis (PCA) in the area of welfare studies. This paper explores the ways discrete data can be incorporated into PCA. The effects of discreteness of the observed variables on the PCA are reviewed. The statistical properties of the popular Filmer and Pritchett (2001) procedure are analyzed. The concepts of polychoric and polyserial correlations are introduced with appropriate references to the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
517
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 669 publications
(534 citation statements)
references
References 56 publications
6
517
0
11
Order By: Relevance
“…At each visit, a household survey was administered to the primary cook of the household consisting of questions addressing household demographics and characteristics related to sanitation, hygiene, and drinking water practices. A socioeconomic status (SES) indicator was developed using polychoric principal component analysis (PCA) (Kolenikov and Angeles, 2009) based on household characteristics and durable goods ownership (household electricity, flooring material, wall material, radio, mobile phone, and bicycle ownership). The continuous PCA variable was divided into quintiles, and the variance explained by the first principal component was 0.535.…”
Section: Household Surveymentioning
confidence: 99%
“…At each visit, a household survey was administered to the primary cook of the household consisting of questions addressing household demographics and characteristics related to sanitation, hygiene, and drinking water practices. A socioeconomic status (SES) indicator was developed using polychoric principal component analysis (PCA) (Kolenikov and Angeles, 2009) based on household characteristics and durable goods ownership (household electricity, flooring material, wall material, radio, mobile phone, and bicycle ownership). The continuous PCA variable was divided into quintiles, and the variance explained by the first principal component was 0.535.…”
Section: Household Surveymentioning
confidence: 99%
“…Kirshnakumar and Nadar (2008) provide an overview of statistical methods of deriving weights based on multivariate statistics, including PCA. On the use PCA to generate an income proxy, see also Kolenikov and Angeles (2009). 4 Brandolini (2007) states that "we should be cautious in entrusting a mathematical algorithm with a fundamentally normative task."…”
mentioning
confidence: 99%
“…34 The index exclusive of housing characteristics is prepared to allow comparisons with the assets index presented in Filmer and Scott (2008). Kolenikov and Angeles (2009) found that ordinal variables perform better than the binary variables used by Filmer and Pritchett (2001) and many subsequent studies. They also found that a 'naive' ordinal coding that records a value of 1 to the lowest standard of asset with higher values given to higher standards in steps of 1, performed adequately in comparison to more computationally intensive alternatives.…”
Section: Annex B: Asset Indicesmentioning
confidence: 70%